Actualization of Letter Terms and Their Derivatives in Religious Style (Linguostylistic Studies, 2016)
The article highlights the problem of actualization of the letter names and their derivatives in the religious style and proves  that it is the Bible that is the source of popularization of the lexicalized and sematicized names of the letters. From the Bible they penetrate and adapt themselves into everyday Ukrainian, that is why modern sermons are full of lexicalized and semanticized names of letters. The author also states that the phraseological units with the names of the letters mainly belong to the biblical texts. It has been clarified that the names of the Greek letters, not the Cyrillic ones, are actualized. This process has been determined by historical conditions.  In fact, the term «letter» as well as its derivatives (literally, in letters,) has been always widely used in the religious style. The names of the letters are used for both nominating and forming pragmatic meanings (the nomination of objects, the formation of a great variety of tropes and figures, the genre peculiarity and a graphic design of the text). Special attention has been drawn to the fact that the lexicalized and semanticized graphemes and idioms containing them, are transferred into other styles of the language from the religious sources. Key words: names of letters, Bible, graphics, lexicalized and semanticized graphemes, nominations, religious style, pragmatic meanings, phraseological units. References